Membangun Kembali Kejayaan Nias melalui Pariwisata (PUNDIMAS: Publikasi Kegiatan Abdimas, 2022)
The purpose of this activity is to raise the spirit of the government ranks and the entire community of West Nias in accelerating development. West Nias Regency has complex development problems. West Nias Regency is a 3T region (outermost, remote, underdeveloped). Yet history records that in the 1940s Nias was a prosperous region. In 1953 Soekarno came to Nias Island to thank him because Nias Island and Aceh had financed negotiations with other countries to maintain independence. Currently, in the outermost small island in West Nias Regency, there are several foreign businessmen managing tourism businesses which are marketed throughout the world but do not provide income for Regional Original Income (PAD) and local community welfare. The implementation method is through a hybrid, namely offline and online zoom meetings. The delivery method uses rhetoric based on the exposure of field data, social media and history. The partner of this activity is the Committee for the 6th Anniversary of the Indonesian West Nias Community Association (PMNBI). The results of the activities obtained are the emergence of enthusiasm and awareness of the development potentials of West Nias which can be processed for the development of West Nias Regency in the future. At the end of the activity, an agreement was also reached with the West Nias Regency Government represented by the Deputy Regent of West Nias and PMNBI represented by the PMNBI Chair to jointly send a letter of request for a hearing with the Deputy for Regional Development of Bappenas and the formation of a Special Economic Zone study team.